2019
DOI: 10.1002/ps.5682
|View full text |Cite
|
Sign up to set email alerts
|

Deorphanization of an odorant receptor revealed new bioactive components for green mirid bug Apolygus lucorum (Hemiptera: Miridae)

Abstract: BACKGROUND The Apolygus lucorum is one of the most destructive insect pests in China with a wide range of host plants. Interaction of A. lucorum with surrounding environment heavily relies on chemical communication. Deorphanization of receptors involved in odors detection elevates our understanding of the olfactory system of this pest and may help to develop a chemical ecology‐based control strategy. RESULTS AlucOR80, an odorant receptor (OR) in A. lucorum was newly cloned. Gene expression analysis showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Among these ligands, methyl salicylate, butyl acrylate and 4-ethylbenzaldehyde excited the strongest response to AlinOR59 in TEVC recordings. Although TEVC values do not represent behavioral activity, we still propose that methyl salicylate, butyl acrylate and 4-ethylbenzaldehyde are behaviorally active. Methyl salicylate was an important semiochemical to insects.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Among these ligands, methyl salicylate, butyl acrylate and 4-ethylbenzaldehyde excited the strongest response to AlinOR59 in TEVC recordings. Although TEVC values do not represent behavioral activity, we still propose that methyl salicylate, butyl acrylate and 4-ethylbenzaldehyde are behaviorally active. Methyl salicylate was an important semiochemical to insects.…”
Section: Discussionmentioning
confidence: 84%
“…A single OR could detect multiple odors, whereas multiple ORs could also detect one odor . Our previous work indicated that AlucOR80 in Apolygus lucorum tuned to 21 ligands and shared four ligands with AlinOR59 including cis -3-hexenyl acetate, hexyl acetate, acetophenone, and ethyl butyrate . Similarly, EsemOR1 in Eriocrania semipurpurella shared the same ligand, β-caryophyllene, with AlinOR59 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations